Geography of a rural service system in India - Wanmali, Sudhir; Wanmali, Sudhir; Wanmali, Sudhir (Delhi : B.R. Pub. Corp., 1987)
Study covers the period, 1968-82.
Revision of the author's two earlier works: Service provision and rural development in India : a study of Miryalguda Taluka ; and, Rural household use of services : a study of Miryalguda Taluka.
Includes index.
Bibliography: p. [205]-213.
Keywords: Rural development -- India -- Miryalguda Taluka -- Longitudinal studies; Household surveys -- India -- Miryalguda Taluka